Textbook Effectiveness with Contextual Teaching and Learning Approach on Creative Thinking Ability Elementary School Students - Sabri, Sabri; Kholil, Umar; Ahmad, Marzuki; Fah, Lay Yoon (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
This research is a development research which aims to develop textbooks with a Contextual Teaching and Learning (CTL) approach to teach the creative thinking skills of Pancasila and Citizenship Education for elementary school students. To achieve the research objectives, Lee & Owens development research was carried out using the ADDIE model which includes analyze, design, develop, implement, and evaluate. In accordance with the product development research criteria, it must meet the criteria of validity, practicality and effectiveness. In this paper, a discussion will be carried out regarding the effectiveness of research products whose process is lifted from the evaluation stage of the research activities carried out. The research subjects were 26 students of Class V SD Negeri 200106 Padangsidimpuan. The object is Teaching Material Products that meet the effectiveness criteria. The product development evaluation stage design uses a one group pretest posttest design. Research instruments include Observation Sheets and Tests. Research conducted shows the application of learning to obtain a score of 3.47 which is in the effective category. Achievement of students' creative thinking abilities with a significance value of 0.01 which is smaller than 0.05 and an N-gain of 0.47 which indicates the product being developed is in the medium category. Thus it is concluded that civics education teaching materials with a contextual teaching and learning approach to teach elementary school students' creative thinking skills are effective. Teaching materials with a contextual teaching and learning approach are very supportive in giving directions to students to provide diverse and varied answers as well as unique answers. Besides that, it is found in active student learning, enthusiastic and enthusiastic in participating in the learning process.